2021
DOI: 10.22456/1679-1916.110211
|View full text |Cite
|
Sign up to set email alerts
|

APA2I - Uma Arquitetura Pedagógica Aberta, Adaptativa e Inteligente para Construção Cooperativa de Conhecimento

Abstract: Este trabalho propõe uma Arquitetura Pedagógica para construção cooperativa do conhecimento, que fomenta a aprendizagem em rede, incentivando a interação e a crítica construtiva, e a mediação distribuída entre alunos e professor. Esta Arquitetura Pedagógica apresenta características inovadoras, por ser aberta, adaptativa e inteligente. Um experimento foi proposto e realizado a partir de um protótipo, que permitiu avaliar a efetividade da Arquitetura. Os resultados apresentaram-se promissores pelos bons níveis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study concluded that the analyzed social network can be a PA since it is intensively mediated by the teacher. [Biancardi et al 2020] presented a PA for cooperative knowledge building. In this PA teacher selects a set of materials called Study Objects (SO).…”
Section: Related Workmentioning
confidence: 99%
“…The study concluded that the analyzed social network can be a PA since it is intensively mediated by the teacher. [Biancardi et al 2020] presented a PA for cooperative knowledge building. In this PA teacher selects a set of materials called Study Objects (SO).…”
Section: Related Workmentioning
confidence: 99%